PENGEMBANGAN KARYA MISIONER DI KEUSKUPAN AMBOINA DI ERA KEPEMIMPINAN Mgr. A. P. C. SOL, MSC SEBAGAI USKUP DIOSIS AMBOINA - Rahawarin, Bernard A. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2015)
This article is meant to be a critical reflection on the pastoral care of Mgr. A.P.C. Sol MSC as the Bishop of the Diocese of Amboina. This is done as an endeavour to try and deepen Msgr. Sol’s missionary spirituality in his pastoral care, as is being formulated in the document Ad Gentes. Various ways of pastoral service as a missionary have become manifest in a number of concrete measures, among others in the fields of spreading the faith (baptism), religious education, formation of activists (aspirant priests/catechists) and caring for and accompanying several religious congregations in the Moluccas. The moment has come that we underline Msgr. Sol’s testimony of religious life and various fields of pastoral care. This cannot be separated from the genuine missionary work i.e. proclaiming the Gospel to all nations.